Menuju Republik Indonesia Serikat - Mangunwijaya, Y. B. (Yusuf Bilyarta), 1929-1999 (Jakarta : Gramedia Pustaka Utama, 1998)
Politics in Indonesia and the need for a federal state; collection of articles.
Includes bibliographical references.
Keywords: Federal government -- Indonesia; Indonesia -- Politics and government -- 1966-